Late favorable results of duroplasty with biocellulose: clinical retrospective study of 20 cases - Mello, Luis Renato; Alcantara, Barbara Bonaparte; Bermardes, Celso Itiberê; Boer, Vitor Hugo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2012)
Objective: Considering the importance of dural replacement in neurosurgery, mainly in times of advanced endoscopic skull base approaches, the authors report the late results after implanting of pure biocellulose membrane in 20 patients harboring different types of lesion, from 1996 to 1999, with objective of demonstrate its use in neurosurgery. Method: The casuistic was followed clinically and image studies were indicated when necessary. Dural substitution was achieved by continuous 4:0 prolene suture without additional glue. Results: The casuistic is constituted by four convexity or parasagittal meningiomas, three single cortical metastasis (melanoma, lung and renal carcinomas), two cerebellar gliomas (one multicentric GBM, one pilocytic cerebellar astrocytoma), one decompressive craniectomy for brain edema due to vasosespasm after aneurysm clipping one decompressive craniotomy for cerebral edema after hemorrhage of a giant fronto-parietal AVM, two mirror MCA aneurysms, one pineal and mesencephalic astrocitoma, one quadrigeminal cistern cyst, one accoustic schwanoma, one spontaneous cerebellar hematoma, one decompressive neurovascular operation for trigeminal neuralgia; 1 cauda equina ependimoma, one lombar myelomeningocele. Currently nine patients are alive, none had direct complication of implant. Recent NMR images of survivors do not show the membrane. Three wound infections could not be definitively attributed to patch. Conclusion: The material was considered safe for dural replacement. Due to inadequate elasticity of pure cellulose, the research was interrupted, waiting for a better product, which is currently being tested.
Keywords: Dura mater/transplantation; brain injuries; neoplasms; prostheses and implants; biocellulose/adverse effects